Analisis Penerapan Perhitungan PPh Final dan Tidak Final atas Penjualan Properti Real Estat (Studi Kasus pada PT XYZ) - Yulius Budi Ariyanto; Ridwan Ridwan (Universitas Warmadewa, 2025)
Ideally, a company should only have one type of tax calculation for reporting the Annual Tax Return. The condition that occurs in one of the real estate property companies in Jakarta has two types of tax calculations, which are Final and Non-Final. This study aims to analyze the impact of the company's Final and Non-Final Income on the applicable tax provisions. This study is descriptive in nature using secondary data that is quantitative in nature. Efforts that can be made by PT X to overcome cases related to the calculation and reporting of Corporate Income Tax are by sorting between Final and Non-Final income, identifying expense accounts arising from the income category and estimating the calculation of the amount of Article 25 Income Tax installments.